2018
DOI: 10.3354/meps12365
|View full text |Cite
|
Sign up to set email alerts
|

Inter-annual climate variability affects foraging behavior and nutritional state of thick-billed murres breeding in the southeastern Bering Sea

Abstract: Sustainability within the fisheries of the commercially important European whelk Buccinum undatum has become a major concern because of over-exploitation and increased landings in many European coastal shelf seas due to the expansion of export markets to East Asian countries. Current management of B. undatum populations is difficult to achieve as several life history traits are problematic to accurately monitor. The current method of age determination for stock assessment has a low success rate and focuses on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Whether a greater abundance of pollock is also beneficial for murres has been unclear, as water masses and prey at depth may be somewhat independent of the dynamics shaping the food web available to surface foragers (Byrd et al 2008b, Renner et al 2016. Our results, however, indicate that common and thick-billed murres shifted towards shelf-based prey on St. George and St. Paul Islands, suggesting that they may also be feeding on juvenile pollock in warm years (Sinclair et al 2008, Kokubun et al 2018. Although all 3 species in both colonies took advantage of more abundant shelf-based prey in warm years in some way, we found that isotopic niche dynamics in the 2 colonies were different between warm and cold years and among species.…”
Section: Effect Of Oceanographic Conditions On Dietmentioning
confidence: 63%
See 4 more Smart Citations
“…Whether a greater abundance of pollock is also beneficial for murres has been unclear, as water masses and prey at depth may be somewhat independent of the dynamics shaping the food web available to surface foragers (Byrd et al 2008b, Renner et al 2016. Our results, however, indicate that common and thick-billed murres shifted towards shelf-based prey on St. George and St. Paul Islands, suggesting that they may also be feeding on juvenile pollock in warm years (Sinclair et al 2008, Kokubun et al 2018. Although all 3 species in both colonies took advantage of more abundant shelf-based prey in warm years in some way, we found that isotopic niche dynamics in the 2 colonies were different between warm and cold years and among species.…”
Section: Effect Of Oceanographic Conditions On Dietmentioning
confidence: 63%
“…The diets of murres and black-legged kittiwakes have been documented to be diverse, including forage fish and invertebrate species (Iverson et al 2007, Sinclair et al 2008, Renner et al 2012. To date, however, efforts to detect broad relationships in this region between the diet of murres and kittiwakes nesting at the Pribilof Islands and regional climate indices have failed to find any consistent trends (Renner et al 2012, 2014, but see Kokubun et al 2018 for thick-billed murres). In contrast, shifting patterns in habitat use have been documented from ship-based surveys at both seasonal and inter-annual time scales (Schneider & Hunt 1984, Renner et al 2016, Suryan et al 2016, Hunt et al 2018.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations